The Influence of Financial Indicators on The Performance of Commercial Banks in Indonesia - Rizky, Filda; Larasati, Tiara Anindya; Muchtar, Susy (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study aims to analyze the effect of financial indicators on the performance of commercial banks in Indonesia, as measured by Return on Assets (ROA). The indicators examined include loan growth (LG), non-performing loans (NPL), loan-to-deposit ratio (LDR), market share (MS), loan loss provision (LLP), cost-to-income ratio (CIR), effective tax rate (ETR), and net interest margin (NIM). A quantitative approach was employed using hypothesis testing and panel data regression analysis on 43 conventional banks listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The results show that LG, LLP, CIR, and ETR have a significant adverse effect on ROA, while LDR and NIM have a significant positive effect. Meanwhile, NPL and MS show no significant effect. These findings highlight that operational efficiency, credit and tax management strategies, and effective fund intermediation are the main determinants of bank profitability. This study is expected to provide practical insights for managerial decision-making and investment evaluation, as well as enrich the academic discourse on the drivers of financial performance in Indonesia’s banking sector. However, this study is limited to a specific data period and does not consider external factors. For future research, the analysis should be expanded to include macroeconomic variables.